Penerapan Algoritma Xtea Dengan Metode Pembangkitan Kunci Linear Congruential Generator Untuk Pengamanan Teks Rahasia - Nusra Anwar; Sinar Sinurat; Imam Saputra (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Confidential text data is very vulnerable to wiretapping by irresponsible parties. The text is still plaintext, making it easier for the attacker to make use of it. Text data can be secured by several techniques. One of them is cryptographic techniques. Cryptographic techniques can secure secret text data by randomizing the hex value of the data into a data that cannot be recognized and read. One of the reliable algorithms is the eXtended Tiny Encryption Algorithm (XTEA) symmetry algorithm. The XTEA algorithm is a simple algorithm that is lightweight and fast in the encryption and decryption process. However, the concept of the symmetry algorithm is the encryption and decryption process using the same key. The security of this concept is very vulnerable if the key is leaked and is public. So that this can be optimized by generating keys using the Linear Congruential Generator (LCG) method. Key generation is used with prime numbers. The key sent to an eligible recipient is only the initial prime number. So that the recipient has to do key assembly first to carry out the decryption process. This can optimize the encrypted ciphertext using the XTEA algorithm.